Pre weaning and post weaning performance of kits from rabbits does exposed to different restriction levels at different periods of gestation - Adeyemo, A.A.; Adeyemi, O. A.; Sogunle, O. M.; Bamgbose, A. M. (Nigerian Journal of Animal Science, 2023)
It is a common practice in commercial rabbit production to feed rabbit does to appetite directly after mating and during gestation. The young does fed ad libitum with diets of high energy level often show parturition problems and excessive fatness; Thus this study aimed to examine whether feed restriction during pregnancy could induce compensatory growth after kindling in growing rabbits. A total of 36 nulliparous does of mixed breeds were randomly assigned into nine treatments of 4 replicates each during pregnancy. The rabbit does were exposed to three levels of quantitative feed restriction (0%, 15% and 30%) at three different periods of gestation (15-19days, 20-24days, 25-29days). At weaning, the kits were subdivided into 4 replicates of 3 rabbits each; thus making 9 treatments of 12 rabbits each making a total of 108 rabbit litters. After weaning, the rabbits were fed ad libitum. Data were collected on pre and post weaning performance. Results obtained showed that kits from rabbit does fed ad libitum during gestation and does on 15% restriction at the 15 - 19th day of gestation recorded significantly (p<0.05) higher mean values for average weight at birth. Post weaning performance showed that weight gain was highest (p<0.05) in kits from does exposed to 15% restriction restricted at the 20 – 24th day of gestation. It can be concluded that maintaining gestating rabbit does on 15% restriction level between the 20th to 24th day and 25th to 29th day of pregnancy will not have adverse effect on their offsprings at growing phase.